Answer:
A = (x + 15)(x + 10) − 5
Step-by-step explanation:
(x+15)(x+10)-5=A would be a solution
To make this easier, let's assign x a value. Let's say 3.
(3+15)(3+10)-5=A
(18)(13)-5=A
234-5=A
A=229
Now with this, we put x in the answer choice and the answer that gives an area of 229 is correct.
A. A=(3+20)(3+10)+12=(23)(13)+12=299+12=311 <u>Answer A is wrong.</u>
B. A=(3+20)(3+10)-12=(23)(13)-12=299-12=287 <u>Answer B is wrong.</u>
C. A=(3+26)(3+15)=(29)(18)=522 <u>Answer C is wrong.</u>
D. A=(3+14)(3+8)=(17)(11)=187 <u>Answer D is wrong.</u>
It's either I'm wrong or the answer choices are wrong.
New answer choices!
A. A=(3+20)(3+11)
=(23)(14)=322 Answer A is wrong.
B. A=(3+15)(3+10)+5
=(18)(13)+5=234+5=239 Answer B is wrong.
C. A=(3+15)(3+10)−5
=(18)(13)-5=234-5=229 Answer C is correct.
D. A=(3+9)(3+10)=(12)(13)=156 <u>Answer D is wrong.</u>
Answer:
a. -5
b.-5
c.-5
Step-by-step explanation:
In order to find the average rate of change of a function , we divide the change in the output value by the change in the input value.
Generally, the average rate of change (ARC) on an ecuatios between two points (x1,f(x1)) and (x2,f(x2)) is
- ARC = [f(x2)-f(x1)]/ (x2-x1)
<em>In case a)</em>
f(-1)= -5*(-1)-8=5-8= -3 f(3)= -5*3-8= -23
Then ARC= (-23-(-3))/(3-(-1))=-20/4=-5
<em>In case b)</em>
f(a)= (-5a-8)
f(b)= (-5b-8)
Then ARC= [(-5b-8)-(-5a-8)]/(b-a)= (-5b+5a)/(b-a)= -5(b-a)/(b-a)= -5
<em>In case c)</em>
f(x)= -5x-8
f(x+h)= -5(x+h)-8= -5x-5h-8
then ARC= [(-5x-5h-8)-(-5x-8)]/(x+h-x) =-5h/h= -5
Answer:
unbias
Step-by-step explanation:
Not asking specific group or person.
Answer:
FOr the first one you can do:
y= -x +4
y= -x+2
y = -x
y= -x-2
y = x-4
Step-by-step explanation:
I'll do the second one in a different answer use these for now.
Answer:
80 meters
Step-by-step explanation:
to find the area multiply length by width